2018
DOI: 10.3390/ma11101841
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Foams: Past, Present, and Future

Abstract: Polymeric foams can be found virtually everywhere due to their advantageous properties compared with counterparts materials. Possibly the most important class of polymeric foams are polyurethane foams (PUFs), as their low density and thermal conductivity combined with their interesting mechanical properties make them excellent thermal and sound insulators, as well as structural and comfort materials. Despite the broad range of applications, the production of PUFs is still highly petroleum-dependent, so this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
393
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(468 citation statements)
references
References 236 publications
1
393
0
9
Order By: Relevance
“…The value of the extinction coefficient of the solid polymer (K W = 600 cm −1 ) was obtained from the literature. 7 The values of the Glicksman extinction coefficients (K G ) calculated using Eqn (6) are presented in Fig. 7.…”
Section: Extinction Coefficient Modelling: Glicksman Extinction Coeffmentioning
confidence: 99%
“…The value of the extinction coefficient of the solid polymer (K W = 600 cm −1 ) was obtained from the literature. 7 The values of the Glicksman extinction coefficients (K G ) calculated using Eqn (6) are presented in Fig. 7.…”
Section: Extinction Coefficient Modelling: Glicksman Extinction Coeffmentioning
confidence: 99%
“…They are also used as a protection during the transport of goods [4,5]. The production of polyurethane foams (PUF) is still dependent on petroleum [6]. The concerns relate primarily to the harmful health effects and environmental problems of oil-based PU and future crude oil shortage [7].…”
Section: Introductionmentioning
confidence: 99%
“…The concerns relate primarily to the harmful health effects and environmental problems of oil-based PU and future crude oil shortage [7]. The development of new technologies motivates searching for solutions based on natural and renewable raw materials with such chemical structure that it will allow their quick and easy degradation [4][5][6][7][8]. The need 2 of 23 to develop a more ecological polyurethane material from renewable sources is also associated with an increasing amount of waste from PU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the effects of manufacturing in a continuous process remains to be explored. (b) PU foams can be tailored through modifications in the chemical formulation [22][23][24]. However, details on the chemical formulation of the PU are rarely documented in the studies found in the literature and they may or may not match those of PU insulated pipes.…”
mentioning
confidence: 99%